MONKS’ RIGHTS UNDER CRIMINAL LAW - แตงทรัพย์ พระมหารมย์; ศุภมนตรี ศิริศักดิ์ (Journal of Buddhist Studies Chulalongkorn University, 2015)
This research examines the state in which the rights of monks originated under criminal law. Monks are citizens of a country. However, the rights of the monk under criminal law are unclearin terms of the procedure taken for monks who commit crime. This causes problem of how monks reserve the rights under such law. Therefore, this thesis will study and analyze rights of monks under criminal law and provide recommendations for improvement of the Clergy Act in order to clarify rights of the monk under criminal law and decrease under criminal law become clearer and problems arising from unclear lawful rights of monks. This study is a qualitative research in law. Criminal procedures taken for monks committing crime, including, arrest, inquiry, criminal prosecution, hearing, judgment and punishment, was studied and analyzed. The Clergy Act, Criminal Code, books, papers and researches were studied and interviews with experts on rights of monks under criminal law were conducted. Research findings revealed that rights of monks under criminal law were not clear and stipulated in a systematic manner. It was only stated that arrests, inquiries, prosecution, judgment process and punishment of monks should be done in a gentle way. This is different from criminal law of the People’s Democratic Republic of Laos, where monks must go through monastic procedure before being prosecuted under criminal law. This added more layers to procedure. After a through study, it was determined that rights of monks under criminal law had to be clearly stated when it came to disrobement, testifying and being held as defendants. During criminal prosecution, a place should be allocated for monks. Finally, monastic court should be established to eliminate ambiguity and complexity of present practices.